Evaluation of Early Childhood Educational Institution Management Program in Improving Accreditation Ratings : Program Evaluation Study with Cipp Model - Gitawidya Amalia; Brigita Puridawaty (Kirana Publisher (KNPub), 2024)
This research aims to evaluate the Early Childhood Education Institution Management program using the CIPP model. This research uses a program evaluation method with the CIPP model, namely analysis of the Context, Input, Process and Product aspects. Mixed method approach, sequential explanatory strategy. Quantitative data collection techniques use questionnaires, and qualitative data collection techniques use source triangulation with observation and interview methods. Interviews were conducted involving relevant regional officials, agency officials, and three PAUD institutions accredited B, C, and not accredited. The population in this study were all private non-formal PAUD institutions in Jatinegara District, East Jakarta, totaling 89 institutions, and the samples were taken using a non-random sampling method with a purposive sample technique. The samples taken were 36 private non-formal PAUD with accreditation status C and non-accredited which had been operational for more than 10 years. The research was conducted from September 2023 to March 2024. The research results showed that all aspects of CIPP received adequate scores in quantitative data analysis and were strengthened by qualitative data. This means that the PAUD program has not been optimally implemented by private non-formal PAUD institutions in Jatinegara District. This is in line with the results of institutional accreditation which is dominated by an accreditation rating of C. The evaluation results show that this program can be continued by providing development based on the needs of PAUD institutions based on this research. The recommendations given are that institutions must have standard operational procedures that are simple and effective, assistance is needed to motivate institutions, and it is necessary to form a PAUD quality control unit that is formed collectively by agency officials.